Effect of the MDM2 promoter polymorphisms SNP309T>G and SNP285G>C on the risk of ovarian cancer in BRCA1 mutation carriers - Bjørnslett, Merete (BioMed Central, 2012)
BACKGROUND: While BRCA mutation carriers possess a 20-40% lifetime risk of developing ovarian cancer, knowledge about genetic modifying factors influencing the phenotypic expression remains obscure. We explored the distribution of the MDM2 polymorphisms SNP309T>G and the recently discovered SNP285G>C in Norwegian patients with BRCA related ovarian cancer. METHODS: 221 BRCA related ovarian cancer cases (BRCA1; n = 161 and BRCA2; n = 60) were tested for the MDM2 polymorphisms. Results were compared to healthy controls (n = 2,465). RESULTS: The SNP309G allele was associated with elevated OR for ovarian cancer in BRCA1 mutation carriers (SNP309TG: OR 1.53; CI 1.07-2.19; p = 0.020; SNP309GG: OR 1.92; CI 1.19-3.10; p = 0.009; SNP309TG+GG combined: OR 1.61; CI 1.15-2.27; p = 0.005). In contrast, the SNP285C allele reduced risk of BRCA1 related ovarian cancer in carriers of the SNP309G allele (OR 0.50; CI 0.24-1.04; p = 0.057). Censoring individuals carrying the SNP285C/309G haplotype from the analysis elevated the OR related to the SNP309G allele (OR 1.73; CI 1.23-2.45; p = 0.002). The mean age at disease onset was 3.1 years earlier in carriers of SNP309TG+GG as compared to carriers of SNP309TT (p = 0.068). No such associations were found in BRCA2 related ovarian cancer. CONCLUSIONS: Our results indicate the SNP309G allele to increase and the SNP285C allele to reduce the risk of BRCA1 related ovarian cancer. If confirmed in independent studies, this finding may have implications to counseling and decision-making regarding risk reducing measures in BRCA1 mutation carriers.